Uses of the Hashtag #Blacklivesmatter: A Quantitative Proposal for Researching Online Social Movements - Cañuelas, Laura; Pintor, Jorge Santiago; Dean-Olmstead, Evelyn; Curbelo, Silvia Álvarez (Journal of New Media and Mass Communication, 2016)
This study presents a process to research the elements that influence the creation and proliferation of the hashtag #BlackLivesMatter, and explores the ways Twitter members use this hashtag. This objective is divided in four questions: What types of events influence the use of the hashtag #BlackLivesMatter?, What type of user generated content appears with this hashtag?, What other hashtags are used when #BlackLivesMatter is present? And which emotions (rage, fear or enthusiasm) appear in these messages? We present a theoretical framework that includes characteristics of microblogging platforms as well as their impact on social movements of the last decade. The methodology uses a quantitative approach to analyze a sample of tweets that contain the hashtag #BlackLivesMatter. The findings indicated that the events that most influences the use of #BlackLivesMatter are the deaths of black people by the hands of police officers, trials and manifestations. Rage is the most common emotion, closely followed by enthusiasm. The user generated content most shared is webpage links and the hashtags that appear most frequently next to #BlackLivesMatter are #Ferguson (427) and #MikeBrown (111). Future investigations should include a wider range of emotions to be evaluated as well as cross platform analysis.